(untitled) (The Pakistan Development Review, 2014)
The relationship between energy consumption and economic growth received a significant amount of attention in energy economics literature [Al-Iraiani (2006)]. Rufael (2006) stated that different energy sources are a necessary requirement for economic and social development and no country in the world has progressed from subsistence economy without the use of energy. In this regard, four views have emerged over time about the relationship between energy consumption and output growth. One point of view is that energy is the prime source of value and other factors like labor and capital cannot do without energy. Many studies argue that the impact of energy use on growth depends on the structure of the economy and the stage of economic growth of the country concerned [Ghali and Sakka (2004)]. The bulk of the literature reports a uni-directional causality from energy consumption to economic growth. When the causality runs from energy consumption to economic growth, it is also called ‘growth hypothesis’. Table 1 provides a list of the studies, which show such results. It implies that an increase in energy consumption has a significant impact on economic growth and if it is positive, then energy conservation policies have a detrimental impact on economic growth. Alternatively, if an increase in energy consumption has significant negative impact on GDP, it implies that growing economy needs a less amount of energy consumption, may be due to shift towards less energy intensive sectors [Payne (2010)]. Second point of view is that economic growth has a positive influence on energy consumption. There may be uni–directional causality from economic growth to energy consumption. Table 1 displays a list of studies showing such results. When the causality runs from economic growth to energy consumption, it is often referred to as ‘conservation hypothesis’. It implies that energy conservation policies formulated to reduce energy consumption may not adversely affect economic growth. Third point of view is that the cost of energy use is very small compared to GDP and consequently its impact on economic growth is nonsignificant. There may be no causality between energy consumption and GDP; it is often referred to as ‘neutrality hypothesis”.